Reciprocal relationships between three aspects of physical self-concept, vigorous physical activity, and lung function: A longitudinal study among late adolescents - Luszczynska, A.; Abraham, Samuel (Elsevier BV, 2012)
Objectives: This prospective study, of older adolescents, investigated relationships between three aspects of physical self-concept, vigorous physical activity and lung function. In particular, physical competence, general appearance evaluations and body areas satisfaction were expected to predict subsequent physical activity, which, in turn, was expected to explain variation in lung function. In line with the reciprocal effect model, bi-directorial relationships were also tested. Gender was expected to moderate hypothesized relationships. Design: A longitudinal design, with three measurement points (baseline, 2-month follow-up, and 14-month follow-up) was employed. Method: 551 late adolescents (15-18 years old) provided self-reported data on physical activity, physical competence, body areas satisfaction, and appearance evaluation. Body weight, height, and a lung function index (forced expiratory volume in 1 s, FEV 1) were measured at baseline and at the 14-month follow-up. Results: Moderated mediation analyses indicated that physical competence at baseline predicted vigorous physical activity (2-month follow-up) among young men and women. Baseline body satisfaction and appearance evaluation were also related to vigorous physical activity (2-month follow-up) and this relationship was stronger for men. Vigorous physical activity predicted FEV 1 (14-month follow-up) and this relationship was stronger among women. The reciprocal pattern of relationships was not confirmed. Conclusions: Findings suggest that health promoting interventions should focus particularly on vigorous physical activity among young women, for example by boosting their physical competence. © 2012 Elsevier Ltd.